Bridge the Gap Between Deaf and Normal - M.J.K Wickramasinghe; Ramanayake U.I.; P.A.N.D Panditharathna; W.M.A.B Wijesinghe; De Silva, Dilshan (International Journal of Engineering and Management Research, 2022)
Communication is the exchange of ideas between individuals. Humans communicate verbally, in writing, or visually. In everyday life, most people communicate verbally. This is because it is the easiest and most efficient method of communication. Although the hearing people communicate verbally, the deaf cannot exchange their thoughts in the same manner. Therefore, people with hearing impairments use the british sign language to communicate with each other. However, it is difficult for the deaf to communicate like the hearing people. In addition, they find it challenging to perpetrate the activities performed by the hearing people in their daily life. Thus, this paper proposes a system that not only enables the deaf to communicate with the hearing people but also performs their daily life activities. The proposed system is able to convert a text in a picture or video into a british sign language and a video in british sign language into standard text. In addition, hearing people can use it to learn the british sign language method.